Overlapping and distinct role of CXCR7‐SDF‐1/ITAC and CXCR4‐SDF‐1 axes in regulating metastatic behavior of human rhabdomyosarcomas - Katarzyna Grymuła; Maciej Tarnowski; Marcin Wysoczynski; Justyna Drukała; Frederic G. Barr; Janina Ratajczak; Magda Kucia; Mariusz Z. Ratajczak (2010)
Abstract We have demonstrated that the α‐chemokine stromal‐derived factor (SDF)‐1‐CXCR4 axis plays an important role in rhabdomyosarcoma (RMS) metastasis. With the recent description of CXCR7, a new receptor for SDF‐1 that also binds the interferon‐inducible T‐cell α chemoattractant (ITAC) chemokine, we became interested in the role of the CXCR7‐SDF‐1/ITAC axis in RMS progression. To address this issue, we evaluated 6 highly metastatic alveolar (A)RMS and 3 less metastatic embryonal (E)RMS cell lines and found that all these cell lines express CXCR7. Although CXCR4 was expressed at a much higher level by highly metastatic ARMS lines, CXCR7 was present at a high level on ERMS lines. We also noticed that CXCR7 expression on RMS cells was downregulated in hypoxic conditions. More importantly, the CXCR7 receptor on RMS cell lines was functional after stimulation with ITAC and SDF‐1 as evidenced by mitogen‐activated protein kinase (MAPK)p42/44 and AKT phosphorylation as well as CXCR7 internalization, chemotaxis, cell motility and adhesion assays. Similarly to CXCR4, signaling from activated CXCR7 was not associated with increased RMS proliferation or cell survival. Moreover, CXCR7 + RMS cells responded to SDF‐1 and I‐TAC in the presence of CXCR4 antagonists (T140, AMD3100). Furthermore, while intravenous injection of RMS cells with overexpressed CXCR7 resulted in increased seeding efficiency of tumor cells to bone marrow, CXCR7 downregulation showed the opposite effect. In conclusion, the CXCR7‐SDF‐1/ITAC axis is involved in the progression of RMS; targeting of the CXCR4‐SDF‐1 axis alone without simultaneous blockage of CXCR7 will be an inefficient strategy for inhibiting SDF‐1‐mediated prometastatic responses of RMS cells.